ALTERNATIF PERHITUNGAN RETURN SHAHIBUL MAL PADA SKEMA MUDHARABAH BANK SYARIAH - Fielnanda, Refky (Fakultas Ekonomi dan Bisnis Islam, 2019)
Abstract: The rapid development of the number of islamic banks should be balanced with the availability of infrastructure to carry out daily operational practices. The operational tools include hardware as like as representative office, computerized system, reliable human resources and software as like as method, culture and financial and islamic banking knowledge. In terms of development of Islamic finance is the paper